Caracterização de pontos de quebras de DNA e rearranjos cromossômicos no gênero Harttia (Siluriformes: Loricariidae) - Deon, Geize Aparecida (2022)
Harttia genus comprises a fish group widely distributed in hydrographic basins of South America. In the cytogenetic point of view, present large karyotypic variation, including an extensive variation in position of ribosomal DNA, B chromosome presence and diversified sex chromosome systems. It is proposed the occurrence of chromosomal instability sites present on the genome of this species could lead the DNA double strand breaks, which trigger these chromosomal rearrangements. Thus, this work aimed to analyze rearrangements and the chromosome involved on karyotypic differentiation in Harttia species, as well the accumulation of repetitive sequence in these regions. Ten species were collected in different hydrographic basins of south, southeast and middlewest regions, including two new not described species. Firstly, classical, and molecular cytogenetic tools were used, including in situ hybridization of ribosomal genes and telomeric sequences, in addition to comparative genomic hybridization essays. The results reveal two new cases occurrence of multiple sex chromosome XX/XY1Y2, besides of new not described species with the highest diploid number founded in the genus. In the investigation of chromosomal rearrangements, was used the microdissection and whole chromosome painting techniques. Were isolated six different chromosomes: 25 (X1) and 26 (X2) from H. punctata, 9 and X (pair 1) chromosome from H. carvalhoi, X chromosome (pair 1) from H. intermontana and chromosome 1 from H. torrenticola. The chromosome painting results using the X1 and X2 probes indicated several chromosomal rearrangements occurred during the diversification of Harttia species from south and southeast regions. With these results, was possible detect that chromosomal breakpoint regions are located inside or surrounding the ribosomal DNA sites in Harttia genome, and these sites triggered several events of chromosomal remodeling. The chromosome painting results obtained with X chromosome probes and chromosome 9 of H. carvalhoi showed that fusion centric events were responsible for the origin of these chromosomes and for decrease in diploid number variation in this lineage. The chromosome 1 of H. torrenticola demonstrated high homeology to chromosome X of H. carvalhoi. Although with similar morphology, the X chromosome of H. intermontana arise from a translocation event between X and autosome (chromosome 9 of H. carvalhoi) besides the identification of other chromosomal rearrangements that triggered the repositioning of homeology blocks on the karyotype of this species. Furthermore, demonstrated two different types of multiple sex chromosome systems founded in the genus, had independent evolutive origin. About the investigation of repetitive sequences associated with this instability regions, were mapped microsatellite sequences and analyzed regarding to the accumulation in chromosomal rearrangements occurred regions. It was observed an enrichment of different sequences in double strand break region. Although a genomic characterization can be necessary to identify the instable sites, the results obtained point to double strand breakpoints in Harttia genome and reaffirm the high karyotypic plasticity in the genus.